The conflicting themes of nonviolence and violence in ancient Indian asceticism as evident in the practice of fasting - Olson, Carl (International journal of Dharma Studies, 2014)
In many ancient Hindu, Jain, and Buddhist texts, the path of the ascetic lifestyle involves an injunction to practice nonviolence, a requirement that conflicts with the violence that the ascetic inflicts upon him/herself by going naked, clothed in coarse garments made of discarded cloth, tree bark, or grass, excessive limits on food in-take, self-mutilation, sleep deprivation, and practicing various forms of extreme austerities in an effort to gain control over one's body, breathing rhythms, and mind. In spite of taking a vow of nonviolence, many Indian ascetics inflict painful harm upon their own bodies that represents a process of marking their bodies, which enables them to create their own bodies in particular ways that distinguish them from ordinary members of society by means of practicing their regimen of discipline. These bodily marks or characteristics make it easy for people within society to recognize their religious status outside of normal social intercourse and on the margins of Indian culture. A popular method of marking an ascetic's body is through extreme forms of fasting, a type of practice pushed to its most excessive extent by the vow to fast unto death by a Jain ascetic. Using fasting as an example of self-inflicted violence by the Indian ascetic, helps us to witness that violence and nonviolence are relative concepts because their degrees of social acceptability differ among religious cultures and even within particular religions. The relative nature of violence and nonviolence can also be traced to its acceptability during changing historical periods and circumstances. Even though violence and nonviolence are relative notions, violence signifies actions that injure, causes harm or pain, or destroys an object, animal, or person, whereas nonviolence is relative to other persons, animals, or things.